Phytochemical content and antioxidant activity of Clinacanthus nutans (Burm. F.) lindau plant parts affected by precooling and storage - Ketaren, Bunga Raya (2017)
Harvesting time is a critical factor affecting yield, phytochemical content, physiological and morphological traits of Clinacanthus nutans (Burm. F.) or ‘belalai gajah’ while the quantity and quality of phytochemicals and antimicrobials vary in different parts of the plant. This study investigated the effects of C. nutans vegetative stage and plant parts on bioactive compounds and phytonutrient retentions, the effects of precooling treatment and storage duration on the quality and phytochemicals of C. nutans, the potential use of the vegetative stage and plant part of C. nutans in phytomedicinal preparations using multivariate analysis, and the effect of precooling methods and storage duration on C. nutans with bioactivity correlation. Three-months old C. nutans plants were harvested at young and mature stages, top of the plants for young leaves and stems, bottom parts for mature leaves and stems. The cleaned samples were stored at 0, 2, 4, 6 and 8 days, and evaluated for moisture and chlorophyll contents, colour, microbial contamination, bioactive compounds, and antioxidant activities. Chlorophyll content of young parts especially of leaves was found to be the highest compared to other parts. For colour, young plant parts were brighter compared to the mature plant parts. TPC, TFC, DPPH scavenging activity and FRAP of young leaves were higher as compared to other parts. Bioactive compounds (vitexin, isovitexin, orientin, isoorientin and shaftoside) of young leaves were significantly higher compared to all vegetative stages. Although C. nutans extracts showed no differences in disc diffusion test against Escherichia coli, Bacillus pumilus and Bacillus cereus, the MIC and MBC were stronger in young parts compared to others. Moisture and chlorophyll contents were affected by interaction between precooling (10 ºC for 10 minutes) and storage duration (0, 2, 4, 6 and 8 days), with a quadratic decrease in throughout storage. Total phenolic content and ferric reducing antioxidant power had negative and quadratic relationships throughout storage duration. Vitexin was affected by interaction between precooling and storage duration. Isovitexin was only affected by precooling and storage duration. Microbial contamination by E. coli, B. pumilus and B. cereus linearly increased during storage. However, hydrocooling exhibited highly positive effects in most of the parameters compared to the ice cooling and control. Nuclear magnetic resonance (1H NMR) in combination with multivariate data analysis PCA and OPLS-DA demonstrated that young vegetative parts of C. nutans contained higher methyl sulphur compound while mature leaves showed higher methyl sulphur compound except cyclocinacoside A and cyclocinacoside A1. 1H NMR and multivariate analysis with ANOVA and regression of clustered metabolites changes upon precooling and storage showed that hydrocooled extracts gave higher metabolites (shaftoside, isoorientin, clinacoside B and citric acid) compared to other treatments. In conclusion, C. nutans young vegetative plant parts contained maximum bioactive compounds and phytochemical contents. Leaves contained higher bioactive compounds, phytochemical contents, and antioxidant activity as compared to stems. Hydrocooling was the best precooling method for two days optimum storage duration.